Viscoelasticity and histology of the human cartilage in healthy and degenerated conditions of the knee - Seidenstuecker, Michael (J Orthop Surg Res, 2019)
BACKGROUND: There are many studies on osteoarthritis, but only a few studies deal with human arthrosis, comparing the mechanical properties of healthy and diseased samples. In most of these studies, only isolated areas of the tibia are examined. There is currently only one study investigating the complete mapping of cartilage tissue but not the difference between instantaneous modulus (IM) in healthy and diseased samples. The aim of this study is to investigate the relationship between the biomechanical and histological changes of articular cartilage in the pathogenesis of osteoarthritis. METHODS: The study compared 25 tibiae with medial gonarthrosis and 13 healthy controls. The IM was determined by automated indentation mapping using a Mach-1 V500css testing machine. A grid was projected over the sample and stored so that all measurements could be taken at the same positions (100 ± 29 positions across the tibiae). This grid was then used to perform the thickness measurement using the needle method. Samples were then taken for histological examinations using a hollow milling machine. Then Giemsa and Safranin O staining were performed. In order to determine the degree of arthrosis according to histological criteria, the assessment was made with regard to Osteoarthritis Research Society International (OARSI) and AHO scores. RESULTS: A significant difference (p < 0.05) could be observed in the measured IM between the controls with 3.43 ± 0.36 MPa and the samples with 2.09 ± 0.18 MPa. In addition, there was a significant difference in IM in terms of meniscus-covered and meniscus-uncovered areas. The difference in cartilage thickness between 2.25 ± 0.11 mm controls and 2.0 ± 0.07 mm samples was highly significant with p < 0.001. With regard to the OARSI and AHO scores, the samples differed significantly from the controls. The OARSI and AHO scores showed a significant difference between meniscus-covered and meniscus-uncovered areas. CONCLUSIONS: The controls showed significantly better viscoelastic behavior than the arthrotic samples in the measured IM. The measured biomechanical values showed a direct correlation between histological changes and altered biomechanics in gonarthrosis.